THE RIGHTS OF THE INTERESTED PERSONS ACCORDING TO â€œTHE LAW OF GEORGIA ON ENFORCEMENT PROCEEDINGSâ€ - Abuseridze, Gocha (European Scientific Journal, ESJ, 2016)
The Administrative Law is a part of public law, as it is depended on the subordinate principle. It aims to realize public interest. On the other hand, Enforcement Law is part of administrative space, which regulates the rules and procedures of the enforcement process for different courtâ€™s decisions as well as other acts. As administrating effects our everyday lives, it is a public interest that this process should be kept in the legal borders. This is exactly what the Administrative Law is all about. It regulates the social relations in which were government and other administrative bodies play a major role. It is true that Enforcement Law provides us with the norms, rules and procedures of the legal administration, but it is still courtâ€™s responsibility to assess the legal quality of it. This is why we need effective justice, to have the competent court ruling practice and to enforce them properly.